Influência da mineralogia dos sedimentos das bacias hidrográficas dos rios Mogi-Guaçu e Pardo na composição química das águas de abastecimento público - Lemes,Marcos José de Lima (2003)
This work studied bottom sediment from catchment area of 13 stations of water treatment of Mogi-Guaçu and Pardo river basins, through identification of mineralogical matrix and its correlation with potential bioavailable metal concentrations. The main clay minerals present were kaolinite and illite. The values of iron and manganese grades were derived from reddish-purple soil, which is rich of such elements. They had higher values on areas with weak vegetation cover compared with other areas linked with more vegetation density. Higher values of calcium at Campestrinho station (IG 69) were associated to occurrence by weathering of calcium feldspars markedly present on regional porphiritic acid rocks. The concentrations of phosphorous are characteristically high on areas near urbanized regions.